Deep in thought while driving: An EEG study on drivers' cognitive distraction - Almahasneh, H. (Elsevier Ltd, 2014)
Our research employed the EEG to examine the effects of different cognitive tasks (math and decision making problems) on drivers' cognitive state. Forty-two subjects participated in this study. Two simulated driving sessions, driving with distraction task and driving only, were designed to investigate the impact of a secondary task on EEG responses as well as the driving performance. We found that engaging the driver's cognitively with a secondary task significantly affected his/her driving performance as well as the judgment capability. Moreover, we found that different features of the secondary task had different effects on EEG responses and different localizations in the frontal cortex. Our hemispheric analysis results showed that the most affected area during distracted driving was in the right frontal cortex region; thus, it is suggested that the activation in the right frontal cortex region may be considered the spatial index that indicated a driver who is in a state of cognitive distraction. Â© 2014 Elsevier Ltd. All rights reserved.